Jalons pour une géographie politique de l’environnement - Lionel Laslaz (L'Espace Politique)
This paper proposes a triple reflection: at first, on the positioning of the geographers who care about environment in the sphere of influence of the political ecology; then, on the place of the nature in the field of the political geography; finally, on the posture adopted by the geographers towards the questions of environment, between justified sensibility, necessary critical distance and clearance guaranteeing of this distance. On the basis of these three reflexive springs, this article presents a contribution to a political geography of environment recognized by its capacity to seize political questions of nature, its ability to form itself as piece of the discipline and its possibility of being freed from any shape of fastenings, just as much directed than blocking its own existence.